(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, fractional calculus approach is applied in solving differential equation which is associated with an electrical circuit i.e. RLC circuit using hypergeometric series. The solution of the fractional differential equation of RLC circuit comes in the form ofMittag-Leffler function and the Ali’s et.al.[8] results are special cases of our main result. Mathematics Subject Classification: 26A33, 33E12.